Accountability of Agency Performance Government in Preventing Fraud With Commitment Organization as Mediator (Case Study in District Fifty Cities) - Zahara, Reza (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2025)
The weak accountability of the performance of government agencies is reflected in the results of the 2021 BPK audit in Fifty Cities Regency which found irregularities in honorarium payments and the use of the budget not in accordance with regional price standards, indicating the weakness of the internal control system and the competence of the apparatus in managing government finances. The purpose of this study was to analyze the accountability of government agency performance in preventing fraud through organizational commitment. The population of the study was the regional apparatus organizations (OPD) in Limapuluh Kota Regency totaling 43 OPDs with sampling using purposive sampling so that the research sample totaled 43 data samples. The data collection technique used a quantitative method approach, namely using a questionnaire filled out by the research sample. Data analysis used path analysis and was processed with the Statistical Package for Social Science (SPSS) version 27. The results of the study found that: (1) the internal control system has an effect on agency performance accountability; (2) the competence of the apparatus has an effect on agency performance accountability; (3) the internal control system has an effect on organizational commitment; (4) the competence of the apparatus has an effect on organizational commitment; (5) organizational commitment has an effect on agency performance accountability; (6) organizational commitment mediates the effect of the internal control system on agency performance accountability; and (7) organizational commitment mediates the effect of apparatus competence on agency performance accountability. The implication of the results of this study is that emphasizing the strengthening of organizational commitment must be the main focus because it is proven to play a significant mediator role between the internal control system and the competence of the apparatus on performance accountability. The recommendation of this study is that the Fifty City Regency Government strengthen its internal control system through periodic audits, transparent reporting, and strict supervision procedures to prevent fraud